1994
DOI: 10.1161/01.str.25.3.566
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic carotid lesions and silent cerebral infarction.

Abstract: Background and Purpose Few studies have investigated the relationships between asymptomatic carotid lesions and silent infarcts confirmed on magnetic resonance imaging.Methods A consecutive series of 117 subjects (average age, 62±9.4 years) who were free from neurological deficit but had at least one established risk factor for stroke were investigated by B-mode carotid ultrasonography and magnetic resonance imaging of the brain. Carotid lesions were evaluated by plaque score, maximum percent stenosis, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
63
1
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 28 publications
7
63
1
1
Order By: Relevance
“…this suggests that the progression of arteriosclerotic change in the brain was paralleled by systemic atherosclerosis and conversely that assessment of systemic atherosclerosis could predict latent damage to the brain, almost similar findings reported by various investigators from different countries. 3,4,5,11,12,13,14 The characteristics of SCI lesions were similar to the results of other studies. 13,15,16,17 that is, they were usually smaller than 1cm,were mostly in the basal ganglia (P<0.01) and had a higher incidence in right cerebral hemisphere (P<0.05) signified non-dominant hemisphere predominance for SCI.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…this suggests that the progression of arteriosclerotic change in the brain was paralleled by systemic atherosclerosis and conversely that assessment of systemic atherosclerosis could predict latent damage to the brain, almost similar findings reported by various investigators from different countries. 3,4,5,11,12,13,14 The characteristics of SCI lesions were similar to the results of other studies. 13,15,16,17 that is, they were usually smaller than 1cm,were mostly in the basal ganglia (P<0.01) and had a higher incidence in right cerebral hemisphere (P<0.05) signified non-dominant hemisphere predominance for SCI.…”
Section: Discussionsupporting
confidence: 87%
“…These findings were consistent with the findings of some other investigators. 12,13,17,18,19,20 although the possibility of embolic events from these lesions could not be wholly excluded because vessels with high grade stenosis showed combined ulcerated lesions. Significant association (P<0.002) and (P<0.001) were found for >50% right internal carotid artery and left internal carotid artery stenosis respectively for ipsilateral >1cm SCI in brain.…”
Section: Discussionmentioning
confidence: 99%
“…While carotid IMT and stenosis have been demonstrated to have strong associations with clinically-evident stroke, 10,14,15 CT-defined infarcts, 16,17 and more recently with MRI-defined infarcts, 18,19 less information is available on relationships of atherosclerosis severity to other MRI abnormalities such as 3 and between ventricular and sulcal enlargement and severity of carotid atherosclerosis. 2 Given the strong and consistent relationships of MRI abnormalities to severity of carotid atherosclerosis, the question arises whether there are other ultrasound-definable characteristics of carotid disease that are related to MRI abnormalities.…”
Section: Carotid Disease and The Brainmentioning
confidence: 99%
“…23,24 The documented ability of B-mode ultrasonographic scanning to detect plaque ulceration, 25 heterogeneity, 26,27 and hemorrhage, 28 though disputed by some, 24,29,30 has led to the demonstration that these ultrasound-defined characteristics are also associated with ipsilateral neurologic symptoms, 31 clinical events, 26 and MRI-defined infarcts. 18,32 The mechanisms by which carotid artery disease may be associated with neurological symptoms and stroke include (1) thrombotic occlusion of large vessels such as the carotid and middle cerebral arteries with hypoperfusion in the vascular distribution supplied by these vessels; (2) cerebral embolism of either atheromatous material from a ruptured or ulcerated carotid plaque or of fibrin-platelet material from a thrombotic plaque to distal vessels; or (3) manifestation or general marker of systemic atherosclerosis occurring at the large and small vessel level. Previous studies have demonstrated a strong relationship between CT-defined small cerebral infarcts and ulcerated carotid plaque, even suggesting that small CT lesions may be markers of active plaque ulceration.…”
Section: Carotid Disease and The Brainmentioning
confidence: 99%
“…While not observed in ACAS, observations from the North American Symptomatic Carotid Endarterectomy Trial (NASCET) and the European Carotid Surgery Trial (ECST) indicate the stroke-risk increases with the degree of carotid narrowing, and is as high as 18.5% over five years for angiographic stenosis between 75% and 94%. 30,31 There is some evidence that the presence of ipsilateral brain infarction on CTor MRI, [31][32][33] and plaque ulceration [34][35][36][37][38] may indicate an increased risk of stroke. Other less well-substantiated risk factors that might worsen the natural history of asymptomatic stenosis include the presence of an occluded contralateral carotid artery, 39 progressive stenosis, 40 a "soft" or echolucent plaque or evidence of intraplaque hemorrhage on ultrasound.…”
Section: Discussionmentioning
confidence: 99%